GEOCHEMISTRY OF THE UNGROUPED CARBONACEOUS CHONDRITE TAGISH LAKE, THE ANOMALOUS CM CHONDRITE BELLS, AND COMPARISON WITH CI AND CM CHONDRITES - Mittlefehldt D.W. (My University, 2002)
I have determined the composition via instrumental neutron activation analysis of a bulk pristine sample of the Tagish Lake carbonaceous chondrite fall, along with bulk samples of the Cl chondrite Orgueil and of several CM chondrites. Tagish Lake has a mean of refractory lithophile element/Cr ratios like those of CM chondrites, and distinctly higher than the Cl chondrite mean. Tagish Lake exhibits abundances of the moderately volatile lithophile elements Na and K that are slightly higher than those of mean CM chondrites. Refractory through moderately volatile siderophile element abundances in Tagish Lake are like those of CM chondrites. Tagish Lake is distinct from CM chondrites in abundances of the most volatile elements. Mean Cl-normalized Se/Co, Zn/Co and Cs/Co for Tagish Lake are 0.68 +/- 0.01, 0.71 +/- 0.07 and 0.76 +/- 0.02, while for all available CM chondrite determinations, these ratios lie between 0.31 and 0.61, between 0.32 and 0.58, and between 0.39 and 0.74, respectively. Considering petrography, and oxygen isotopic and elemental compositions, Tagish Lake is an ungrouped member of the carbonaceous chondrite clan. The overall abundance pattern is similar to those of CM chondrites, indicating that Tagish Lake and CMs experienced very similar nebular fractionations. Bells is a CM chondrite with unusual petrologic characteristics. Bells has a mean CI-normalized refractory lithophile element/Cr ratio of 0.96, lower than for any other CM chondrite, but shows CI-normalized moderately volatile lithophile element/Cr ratios within the ranges of other CM chondrites, except for Na which is low. Iridium, Co, Ni and Fe abundances are like those of CM chondrites, but the moderately volatile siderophile elements, Au, As and Sb, have abundances below the ranges for CM chondrites. Abundances of the moderately volatile elements Se and Zn of Bells are within the CM ranges. Bells is best classified as an anomalous CM chondrite.